2021
DOI: 10.1002/dev.22216
|View full text |Cite
|
Sign up to set email alerts
|

Midfrontal theta oscillations and conflict monitoring in children and adults

Abstract: Conflict monitoring is central in cognitive control, as detection of conflict serves as a signal for the need to engage control. This study examined whether (1) midfrontal theta oscillations similarly support conflict monitoring in children and adults, and (2) performance monitoring difficulty influences conflict monitoring and resolution. Children (n = 25) and adults (n = 24) completed a flanker task with fair or rigged response feedback. Relative to adults, children showed a smaller congruency effect on midf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…During the first 5 y of life, children are subjected to rapid developmental changes in core cognitive functions that underlie performance monitoring and voluntary regulation of behavior (e.g., detection and correction of errors) [ 31 , 32 ]. Preschool children are less efficient than adults in monitoring and regulating their actions adaptively [ 33 , 34 ]. However, they engage the same neurocognitive control processes as adults to detect and to correct erroneous responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first 5 y of life, children are subjected to rapid developmental changes in core cognitive functions that underlie performance monitoring and voluntary regulation of behavior (e.g., detection and correction of errors) [ 31 , 32 ]. Preschool children are less efficient than adults in monitoring and regulating their actions adaptively [ 33 , 34 ]. However, they engage the same neurocognitive control processes as adults to detect and to correct erroneous responses.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding PEA, three studies [ 34 , 38 , 42 ] showed a significant correlation between ERN and PEA in children from 5- to 8-year old, which suggested a role of ERN in predicting performance recovery during childhood. Finally, no studies have been found on the link between frontal theta oscillations and post-error behavioral compensation, despite growing evidence that suggested a key role of theta oscillations in orchestrating different cognitive control demands across preschool and school ages [ 33 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, when applied externally through transcranial alternating current stimulation (tACS), midfrontal theta modulated behavioral adjustments following errors in a Flanker task (Fusco et al, 2018). It is thought that midfrontal theta originates from the anterior cingulate cortex (ACC) and is cognitively associated with the monitoring of the errors (Botvinick, Cohen, & Carter, 2004;Cavanagh, Cohen, & Allen, 2009;Chevalier, Hadley, & Balthrop, 2021;Cohen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Midfrontal theta has been associated with the processing of cognitive conflict in various tasks, including the Stroop task (e.g., Eschmann & Mecklinger, 2021;Hanslmayr et al, 2008), the Eriksen flanker task (e.g., Chevalier et al, 2021;Cohen et al, 2008;Giller et al, 2020;Pscherer et al, 2020), the Simon task (e.g., Töllner et al, 2017;van Driel et al, 2012), and the responsepriming task (e.g., Pastötter et al, 2010Pastötter et al, , 2013. In addition, fronto-central event-related potential (ERP) negativities such as the conflict-related N2 (a negative deflection peaking around 250 to 350 ms after stimulus onset; Boenke et al, 2009) or the response-locked FRN (feedback-related negativity, peaking 80 ms before response onset) share a common spectral signature, namely midfrontal theta (Cavanagh et al, 2012;Heidlmayr et al, 2020).…”
Section: Introductionmentioning
confidence: 99%